PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH KABUPATEN/KOTA PROVINSI SULAWESI TENGAH - Rasyid, Moh. (Katalogis, 2018)
The aims of this research are: 1). To find out about general allocation funds, specific allocation funds, profit sharing funds, and local revenue on regional expenditure of regency/City in Central Sulawesi; 2) To explore simultaneous influence of general allocation funds, specific allocation funds, profit sharing funds, and local revenue on regional expenditure of regency/City in Central Sulawesi; 3) To explore partial influence of general allocation funds, specific allocation funds, profit sharing funds, and local revenue on regional expenditure of regency/City in Central Sulawesi. The research method is panelÂ data regression with software Eviews 9.0. Sample consist of 11 regencies/Cities in Central Sulawesi Province in 2012-2014. The results find that general allocation funds, specific allocation funds, profit sharing funds, and local revenue have influenced regional expenditure 0f 95.37%, While the remaining influenced by factors that are not studied. It also finds that general allocation funds, specific allocation funds, profit sharing funds, and local revenue have simultaneous influence on regional expenditure of regency/City in Central Sulawesi. Partially, general allocation funds and and local revenue have significant influence on regional expanditure in Central Sulawesi. This in indicated by the t-value higher than t-table or probability value is smaller than 5%.